The solar wind heavy ion composition in the ascending phases of the solar cycles 23 and 25 - Carpenter, D. T.; Lepri, S. T.; Zhao, L.; Dewey, R. M.; Raines, J. M.; Livi, S.; Galvin, A. B.; Kistler, L. M. (Frontiers in Astronomy and Space Sciences, 2024)
The approximately 11-year solar cycle has been shown to impact the heavy ion composition of the solar wind, even when accounting for streams of differing speeds; however, the heavy ion composition observed between the same specific phases of a past solar cycle and the current cycle has rarely, if ever, been compared. Here, we compare the heavy ion composition of the solar wind, as measured in situ during the solar cycle 23 and 25 ascending phases. We examine the mean iron and oxygen charge state composition and the O7+/O6+ ratio in multiple ranges of associated bulk wind speeds. Then, we compare the iron and oxygen charge state composition and relative abundance of iron to oxygen in the traditionally defined fast and slow solar wind. Finally, to determine the impact of individual ion contributions on the solar wind iron abundance, we examine individual ratios of iron and oxygen ions. Although the charge state composition remained broadly similar between these two ascending phases, both the O7+/O6+ ratio and iron fractionation in fast-speed streams were higher in the solar cycle 25 ascending phase than they were during the solar cycle 23 ascending phase, suggesting that equatorial coronal hole fields more frequently reconnected with helmet streamers or active regions in the latter of the two ascending phases; however, more work will need to be done to connect these observations back to their coronal origins. The individual ion ratios used in this work provided a spectrum to analyze the aggregate elemental abundances, and this work, as a whole, is an important step in determining how conditions in the corona may vary between solar cycles between the same phases.